Cytoplasmic RNA Extraction from Fresh and Frozen Mammalian Tissues - P. Carninci; M. Nakamura; K. Sato; Y. Hayashizaki; M.J. Brownstein (BioTechniques, 2002)
The quality of collections of expressed sequence tags and full-length cDNAs is adversely affected by the presence of “junk” clones derived from unspliced or partially spliced RNAs present in conventional total RNA preparations. One can overcome this problem by using intact cytoplasmic RNA to create cDNA libraries, but the methods in the literature that describe the preparation of RNA only work well for extracting cultured cells. Cell lines are not as diverse as one would like, and to clone comprehensive sets of human and model organism full-length cDNAs, libraries have to be prepared from tissue samples. Thus, we have developed a robust and inexpensive method that allows intact cytoplasmic RNA to be extracted from both fresh and frozen mammalian tissues. A mouse full-length, captrapped cDNA library prepared with RNA using this new procedure had excellent characteristics.